Market Orientation And Business Performance: Insights From Recent Research Trends And Cluster Analysis - Indarwati, Tias; Paramita, R.A. Sista; Kautsar, Achmad; Asandimitra, Nadia (CV ODIS, 2024)
Business performance is a critical aspect that demands significant attention from firms as it serves as the primary determinant of organizational success and sustainability. The literature suggests that market orientation plays a pivotal role in influencing business performance outcomes. This study employs VOS Viewer to analyze data from 64 relevant articles identified from the Scopus database in the fields of Business, Management and Accounting, Economics, Econometrics and Finance, and Social Science. The cluster analysis reveals five clusters: Cluster 1 - Entrepreneurial Competitive Advantage in SMEs, Cluster 2 - Performance-Driven Green Management, Cluster 3 - Focused Strategy in Family Business, Cluster 4 - Information-Driven Customer Service, and Cluster 5 - Impact-Driven Small Market Enterprises. Entrepreneurial orientation and innovation have proven crucial in shaping the competitive advantage and business performance of SMEs, with market orientation significantly aligning organizational strategies with market demands and customer needs. This strategic approach enhances market responsiveness, innovation, and competitive advantage of SMEs in a dynamic and competitive business environment.